Pengaruh Tarif Pajak dan Kepemilikan Asing terhadap Penerapan Transfer Pricing untuk Penghindaran Pajak - Miladiah Kusumaningarti; Puji Rahayu; Yunicha Yunicha (Jurnal Riset Akuntansi, 2025)
The purpose of this study is to determine the effect of tax rates (X1) and foreign ownership (X2) on the application of transfer pricing (Y) for tax avoidance (Z). Case study of consumer goods manufacturing companies listed on the IDX for the 2017-2021 period. The population of this study was 63 companies in the consumer goods sector and 7 companies were selected as samples according to the criteria in purposive sampling. The analisys technique used in this study is multiple linier analisys, which was previously tested first with the classical assumption test. The results of this study indicate that partially tax rates do not affect transfer priing and foreign ownership partially affects transfer pricing. However, simultaneously does not affect transfer pricing. The correlation coefficient value shows that all independent nvariables have an influence of 76.3 the rest is explained by other variables outside the study. Based on the path analys test, the results show that tax rates affect tax avoidance while foreign ownership and transfer pricing do not affect tax avoidance. The correlation coefficient value shows that tax rates, foreign ownership and transfer pricing on tax avoidance are 67.1 on the next variable, 32,9 the rest is explainedby other variables outside the study.